Conceptualising Restorative Justice within Transitional Justice Framework - Jaynes, Natalie (Department of Political Studies, 2014)
The concept of 'restorative justice' has in recent years been widely invoked in the transitional justice literature. The term is however often used loosely, inconsistently and in apparently different senses. This minor dissertation addresses this dilemma by bringing together three influential bodies of work on restorative justice and exploring what each body of work means by the term 'restorative justice'. The three bodies of work are that of Archbishop Desmond Tutu, criminal justice theorists and accounts of African Traditional Justice Mechanisms. With a clearer picture of what these respective sources mean when referring to restorative justice, the discussion then turns to the potential relevance and significance of these conceptions of restorative justice for transitional justice. The three bodies of work on restorative justice, while distinct in their own right, are brought into conversation through applying a uniform methodology. This methodology draws on John Rawls' distinction between concept and conception. Given that restorative justice is not concerned with the rules of ordinary language usage a conceptual analysis is not possible. What is possible is to follow a route of enquiry that explores the different conceptions of restorative justice reflected in each body of work. These conceptions are discussed against the backdrop of a transitional justice framework. This minor dissertation does not make any claims regarding the concept of restorative justice. Rather what are delivered are some findings about the conceptions of restorative justice that feature within the three bodies of work under discussion. The conceptions of 3 restorative justice differ in certain respects but also overlap in others. The crucial point of overlap concerns a sociological or relational approach to crime and wrongdoing which requires that all parties to a conflict are involved in its resolution. Herein lies the chief contribution of restorative justice to transitional justice, namely that restorative justice embodies what Jon Elster deems to be the task of transitional justice - that a society judge itself.